PERSPEKTIF GENDER DALAM PARTISIPASI PETANI PADA PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) TANAMAN SAYURAN DI KECAMATAN KERSAMANAH KABUPATEN GARUT PROVINSI JAWA BARAT - farida liani; dwiwanti sulistyowati; o'eng awarudin (Politeknik Pembangunan Pertanian Bogor, 2018)
ABSTRACT The ministry of agriculture has implemented the Sustainable Food House ares (SFHA) program to increase women’s participation in the agricultural sector. the study aims to analyze the level of farmer participation in the program SFHA gender perspective, analyze the factors that influence farmers participation in the SFHA program gender perspective dan develop strategies to increase farmer participation in the SFHA program. The reseach was conducted from April to June 2018. The reseach population of 150 farm households, spread in 6 groups of women farmers who implement the program SFHA. A sample of 60 farm households selected using a simple ramdom technique. The research variables consisted of the characteristics of farmers, extension activities, role of extension and farmer participation. Data were analyzed with descriptive statistical analysis and inferential statistic that is multiple linear regression, Independent T Test different test and Kendall's W concordance test. The results showed that there was a very real difference between female farmers and male farmers in the SFHA program, the participation of women farmers is higher than that of male farmers. Factors affecting the participation of women farmers and male farmers in the SFHA program are extension activities and extension roles. Strategies that can be done to increase the participation of farmers is to intensify extension activities, adjust the material, methods and media with the situation of farmers and strengthening the role of extension facilitators, communicators and motivators. Keywords: gender, participation, peasant woman,SFHA ABSTRAK Kementerian Pertanian telah melaksanakan program Kawasan Rumah Pangan Lestari (KRPL) untuk meningkatkan partisipasi perempuan pada sektor pertanian. Penelitian ini bertujuan untuk menganalisis tingkat partisipasi petani pada program KRPL perspektif gender, menganalisis faktor-faktor yang mempengaruhi partisipasi petani pada program KRPL perspektif gender dan menyusun strategi untuk meningkatkan partisipasi petani pada program KRPL. Penelitian dilaksanakan mulai April sampai dengan Juni 2018. Populasi penelitian sebanyak 150 rumah tangga tani, tersebar di enam kelompok wanita tani yang melaksanakan program KRPL. Sampel penelitian sebanyak 60 rumah tangga tani yang dipilih menggunakan teknik acak sederhana. Variabel penelitian terdiri atas karakteristik petani, kegiatan penyuluhan, peran penyuluh dan partisipasi petani. Data dianalisis dengan analisis statistik deskriptif dan statistik inferensial yaitu regresi linier berganda, uji beda Independent T Test dan uji konkordasi Kendall’s W. Hasil penelitian menunjukkan terdapat perbedaan yang sangat nyata antara petani perempuan dan petani laki-laki pada program KRPL, partisipasi petani perempuan lebih tinggi dibandingkan dengan petani laki-laki. Faktor-faktor yang mempengaruhi partisipasi petani perempuan dan petani laki-laki pada program KRPL adalah kegiatan penyuluhan dan peran penyuluh. Strategi yang dapat dilakukan untuk meningkatkan partisipasi petani adalah dengan mengintensifkan kegiatan penyuluhan, menyesuaikan materi, metode dan media dengan keadaan petani serta memperkuat peran penyuluh sebagai fasilitator, komunikator dan motivator. Kata kunci: gender, partisipasi, wanita tani, KRPL